Analysis of Financial Statements in Companies Drinking Water Area Banggai Islands Regency - Rosfianti M.Yadasang; Yusni; Rosma Ndiak (Fakultas Ekonomi Universitas Muhammadiyah Palu, 2024)
The aim of this research is to determine the level of Liquidity, Profitability and Activity in the Regional Drinking Water Company of Banggai Islands Regency for the period 2019 - 2021. The type of data used in this research is qualitative and quantitative data. Data collection techniques used are observation, interviews and documentation. The data analysis techniques used are Liquidity Ratios, Profitability Ratios, and Activity Ratios. From the Research Results, Analysis of Liquidity Ratios for 3 Years Based on the Current Ratio and Quick Ratio Calculations of the Regional Drinking Water Company of Banggai Islands Regency in 2019, the Current Ratio was 184.40% and the Quick Ratio was 316.58%, in 2020 the Current Ratio was 228.77 % and Quick Ratio of 413.12%, in 2021 the Current Ratio is 218.28% and the Quick Ratio is 496.20%. Thus, it shows that the liquidity ratio is in good condition because the current assets owned can fulfill financial obligations on time. Profitability Ratio Analysis for Three Years Based on Calculation of Return on Equity and Return on Investment of the Regional Drinking Water Company of Banggai Islands Regency. In 2019, Return On Equity was 31% and Return On Investment was 10%, in 2020 Return On Equity was 43% and Return On Investment At 20%, in 2021 Return On Equity will be 33% and Return On Investment will be 67%. Thus, it shows that the profitability ratio is in very good condition because the company is able to make a profit using its own capital and the company is able to generate profits which will be used to cover the investments made so that the company's profits for three consecutive years’ experience a profit. Activity Ratio Analysis for 3 Years Based on the Total Asset Turnover Calculation of the Regional Drinking Water Company of Banggai Islands Regency in 2019, it was 29 times, in 2020 it was 30 times, in 2021 it was 32 times. Thus, it shows that the activity ratio is in good condition because the company can generate more sales with certain levels of assets, and vice versa.